Digital Alienation and Identity in "Don DeLillo’s White Noise" and Contemporary Arabic Fiction - Umniyah Mohammed Jasim, Asst.Lect. (lark, 2026)
This paper discusses digital disconnection and the search for identity by comparing Don DeLillo’s White ‎Noise, published in 1985 with some Arabic novels that were published after 2000. DeLillo’s novel is one ‎of the most important works of postmodernism as it presents a reality that has been overtly saturated by ‎media abundance and technological revolution where human experience becomes commodified. ‎Contemporary Arabic literature, Iraqi, and Arab fiction after 2000 spoke about similar issues in different ‎sociopolitical contexts. Works like Frankenstein in Baghdad by Ahmed Saadawi show the reader how ‎technology and media can be associated with violence, memories, and feelings of alienation that take place ‎within a postwar environment. By contrast, these narratives bring out similarities and differences in the ‎representation of identity in technologically influenced societies. The paper thus becomes a study of how ‎American and Arabic writers respond to the same questions: In what ways does technology reshape self-‎identity? Which media narratives replace individual memory and identity? The comparative framework ‎demonstrates that despite coming from different backgrounds, both literary traditions engage with the same ‎universal problem – technological intervention in human identity – thus foregrounding the way ‎comparative literature maps cross-cultural modes of estrangement even as it registers cultural specificity.‎
Keywords: digital alienation, identity, Arabic novel, comparative literature, media culture